Learning objectives a key to better teaching - Felder, Richard M. (IEEE, 2013)
The goal of this tutorial is to teach instructors how to craft learning objectives. First, we'll explore the importance of writing learning objectives. Then, we'll examine the components of a properly written learning objective, and apply that knowledge as we evaluate learning objectives. Next, you'll try your hand at writing two learning objectives and then apply Bloom's Taxonomy of Educational Objectives to the objectives you developed
Description based on online resource; title from title screen (IEEE Xplore Digital Library, viewed November 17, 2020)
Keywords: Training; Writing; Film